1982
DOI: 10.1021/jm00352a013
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and serotonin receptor properties of 4-substituted derivatives of the hallucinogen 1-(2,5-dimethoxyphenyl)-2-aminopropane

Abstract: The serotonin (5-HT) receptor affinities and behavioral (discriminative stimulus) properties of a series of 4-substituted derivatives of 1-(2,5-dimethoxyphenyl)-2-aminopropanes (2,5-DMA) were investigated. The substituents at the 4-position included H, OMe, OEt, Me, Et, F, Br, I, and NO2. Substituent lipophilicities (pi values) of these functionalities appear to have a minimal effect on either 5-HT receptor affinity or behavioral activity. Those derivatives previously found to be most potent in human studies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 3 publications
0
46
1
Order By: Relevance
“…[145] a-Methylation of the phenethylamines to their corresponding phenylisopropylamines leads to the most potent compounds, such as DOM (15), DOB (16), and DOI (17). [146][147][148] A significant increase in potency was observed from compound 10 (ED 50 = 5.6 mmol kg À1 ) to (AE )-15 (ED 50 = 1.8 mmol kg À1 ) in DD studies, [149] and in human clinical studies. [117,144] However, an affinity study using rat brain […”
Section: Classic Phenylalkylaminesmentioning
confidence: 99%
“…[145] a-Methylation of the phenethylamines to their corresponding phenylisopropylamines leads to the most potent compounds, such as DOM (15), DOB (16), and DOI (17). [146][147][148] A significant increase in potency was observed from compound 10 (ED 50 = 5.6 mmol kg À1 ) to (AE )-15 (ED 50 = 1.8 mmol kg À1 ) in DD studies, [149] and in human clinical studies. [117,144] However, an affinity study using rat brain […”
Section: Classic Phenylalkylaminesmentioning
confidence: 99%
“…There- fore, an investigation was undertaken in order to determine which of a series of phenalkylamines was capable of producing effects similar to those of 5-)Me DMT. The training dose employed for 5-OMe DMT was 3.0 mg/kg; the phenalkylamines included 36 phenylisopropylamines and/or isomers. 71 The results of this study allowed the differentiation of phenalkylamine derivatives on the basis of their stimulus properties.…”
Section: A9-thc"mentioning
confidence: 99%
“…However, there is a significant ( r = 0.964) correlation between the ED,,values of 1 4 phenylisopropylamines and their total human hallucinogenic dose. 36 Although it is not being suggested that the use of the discriminative stimulus paradigm, with DOM (1.0 mglkg) as the training drug, serves as a model or predictor of human hallucinogenic potency, there certainly exists a relationship between human hallucinogenic potency and discrimination-derived data. To further challenge this relationship, ED,, values were determined for several additional agents and Figure 7 shows a plot of log Iltotal human hallucinogenic dose (pmoles) vs log I/ED,, (pmbleslkg) for the extended series of compounds.…”
Section: Correlation Studiesmentioning
confidence: 99%
“…Therefore, it appears that inhibition of MAO is not involved in the ocular hypotensive response observed for 5-HOAMT, 5-MeOAMT, and R-DOI. 5-MeODMT (Weil and Davis, 1994), 5-MeOAMT (Kantor et al, 1980), and R-DOI (Glennon et al, 1982) have been shown to enter the central nervous system following systemic dosing, suggesting that a centrally mediated mechanism may be responsible for the reduction in IOP observed with 5-HT 2 agonists. However, the nonselective peripheral 5-HT 2 agonists 5-HOAMT (Baudrie and Chaouloff, 1992;Okada et al, 1995) and 5-HODMT (McBride, 2000) also decreased IOP in the monkey following topical administration.…”
mentioning
confidence: 99%